Organizational And Pedagogical Conditions Of Teaching The Subject Information Communication Technologies And Systems In The Economy - Yuldashev Shadiyor Shuxrat ogli; Bazarbayev Murotjon Xolmamat ogli (Academia One Publishing, 2025)
The article discusses the organizational and pedagogical conditions necessary for effectively teaching the subject "Information Communication Technologies and Systems in the Economy" in higher education institutions. It examines the integration of digital tools, learning management systems (LMS), interactive teaching formats, and student-centered approaches. The study emphasizes the importance of qualified instructors, updated curricula, infrastructure readiness, and institutional support in fostering competence development in ICT for economics students.
Keywords: Information communication technologies; economic education; organizational support